On the identity of Anchorosternum sinense(Coleoptera: Hydrophilidae: Megasternini) - Fikáček, Martin; Jia, Fenglong (Zootaxa, 2011)
The monotypic genus Anchorosternum Jia, Wu, & Pu, 2001 (Hydrophilidae: Sphaeridiinae: Megasterinini) was originally described to accomodate A. sinense Jia, Wu & Pu, 2001, then known from four specimens collected in dung in  southern China. At the time of its description, Jia. et al. (2001) were unable to compare it with type material of other megasternine taxa occurring in the Oriental region, and as such the genus was largely diagnosed using the key to megasternine genera published by Hansen (1991), which also can be difficult to use without compartive material at hand. Moreover, all four type specimens were lost when the entomological collection of Sun Yat-sen University (formerly Zhongshan University) in Guangzhou, P. R. China, moved to a new building. Consequently, Anchorosternum remained the last megasternine genus with unclear status following the revision of recently described hydrophilid genera by Short & Fikáček (2011) and the revision of the Megasternini described previously by the Chinese authors by Jia et al. (2011).